2018
DOI: 10.1257/aer.20162015
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Mobility and Preferences for Redistribution

Abstract: Using new cross-country survey and experimental data, we investigate how beliefs about intergenerational mobility affect preferences for redistribution in France, Italy, Sweden, the United Kingdom, and the United States. Americans are more optimistic than Europeans about social mobility. Our randomized treatment shows pessimistic information about mobility and increases support for redistribution, mostly for “equality of opportunity” policies. We find strong political polarization. Left-wing respondents are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
578
6
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 695 publications
(643 citation statements)
references
References 63 publications
48
578
6
11
Order By: Relevance
“…With respect to the "attention check", only 0.82% of the respondents reported inattention during our survey. We used the same question used by Alesina, Stantcheva, and Teso (2016), and these types of questions have been shown by Meade and Craig (2012) to identify careless survey takers, as well as enhance respondent's attention in the questions that follow. The reason why we asked individuals their levels of trust regarding the national government, major companies, and other seven groups/organizations is twofold.…”
Section: First Stage and Magnitude Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the "attention check", only 0.82% of the respondents reported inattention during our survey. We used the same question used by Alesina, Stantcheva, and Teso (2016), and these types of questions have been shown by Meade and Craig (2012) to identify careless survey takers, as well as enhance respondent's attention in the questions that follow. The reason why we asked individuals their levels of trust regarding the national government, major companies, and other seven groups/organizations is twofold.…”
Section: First Stage and Magnitude Of Resultsmentioning
confidence: 99%
“…The main conclusion be comparing column 1 and 4 is that the populations are strikingly similar. Kuziemko, et al (2015) collected their sample between January 2011 and August 2012, and at least with respect to observables, it is 31 In a follow up survey that is explained in section 6, we introduced an "attention check" question mid-way through the survey as in Alesina, Stantcheva and Teso (2016). Only 0.82% of respondents reported some form of inattention at that point.…”
Section: Survey Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case, we take ψ (a) = 0 for a < 1 and b (z) = 0, so that agents are only influenced by incomes higher than theirs. One motivation is that people might be overconfident about their probability of achieving high incomes, as they are optimistic about mobility in general (as in Bénabou and Tirole (2006a); Alesina, Stantcheva and Teso (2018)). Another might be that the top rates are very salient.…”
Section: Optimal Income Tax Formulamentioning
confidence: 99%
“…Some recent works have shown that preferences for redistribution differ between mobile and non-mobile individuals (Alesina, Stantcheva and Teso 2017;Gugushvili 2016;Siedler and Sonnenberg 2013;Steele 2015), but they do not focus specifically on the effect of class mobility. Departing from previous studies, we use the diagonal reference model (Sobel 1981(Sobel , 1985 to examine the relative effect of social origin and destination classes on individual preferences for redistribution in a large sample of European countries.…”
Section: Introductionmentioning
confidence: 99%